Cover Picture: Selective Synthesis of Oligosaccharides by Mechanochemical Hydrolysis of Chitin over a Carbon‐Based Catalyst (Angew. Chem. Int. Ed. 3/2023) - Kobayashi, Hirokazu; Suzuki, Yusuke; Sagawa, Takuya; Saito, Makoto; Fukuoka, Atsushi (Angewandte Chemie International Edition, 2023)
Mechanochemical approaches enable the efficient synthesis of a variety of chemicals. Hirokazu Kobayashi, Atsushi Fukuoka et al. report in their Research Article (e202214229) that an activated carbon catalyst with weak acid sites converts chitin, an abundant but highly recalcitrant biomass, selectively into chitin‐oligosaccharides under ball‐milling conditions. Large chitin molecules are hydrolyzed more rapidly than small oligomers, leading to a high selectivity. The produced oligosaccharides enhance plant immune systems so that crops can withstand pathogens with low agrochemical use.